Correlation between nomophobia, fear of missing out and academic success - Çatıker, Aslıhan; Bulucu Büyüksoy, Gizem Deniz; Özdil, Kamuran (Journal of Dependence, 2022)
Objective: The aim of the study was to determine the relationship between nomophobia and fear of missing out with academic performance among nursing students. Method: This cross-sectional research was performed with students in the nursing department of a health sciences faculty in a university in Turkey. The study was completed with 241 participants attending the nursing department. Data were collected with the descriptive survey form, nomophobia questionnaire (NMP-Q), and fear of missing out scale (FoMOs). Results: The research determined that nursing students had mean NMP-Q (73.82±21.27) and FoMOs (21.36±6.93) points at average levels. The model in the research was significant and the variables of gender and income explained 17% of general point average (GPA). Accordingly, GPA was lower by 2.4 points for men and by 0.9 points for those whose income did not match their expenditure Conclusion: The study identified that NMP-Q and FoMOs points were at moderate levels and these did not have an effect on the academic success level of nursing students. However, considering the seriousness of problems created by increasing technology use and digital problems currently, taking precautionary measures against these problems will be an effective intervention.